A recent review on phytochemical constituents and medicinal properties of kesumv(Polygonum mins Huds.) - Vikram, P.; Chiruvella, K.K.; Ripain, I.H.A.; Arifullah, A.
Medicinal plants and herbal preparations are gaining renowned interest in scientific communities nowadays due to their reliable pharmacological actions and affordability to common people which makes them effective in control of various diseases. Polygonum minus (Polygonaceae) locally known as kesum is an aromatic plant commonly used in Malay delicacies. The plant is having potential applications due to its high volatile oil constituents in perfumes and powerful antioxidant activity. It has been used traditionally to treat various ailments including dandruff. The research has been carried out by various researchers using different in vitro and in vivo models for biological evaluations to support these claims. This review paper may help upcoming research activities on Polygonum minus by giving up to date information on the phytochemical constituents and medicinal properties of kesum to a possible extent with relevant data